Dissecting crime news: capturing the value of stories / Sharon Wilson, Faridah Ibrahim. - Sharon, Wilson; Ibrahim, Faridah (CMIWS and UiTM Press, 2010)
The study explored factors which make up news values in reference to various literature and scholars specifically in crime news reporting by Jewkes (2004) the researcher discovered various expected similarities and examined the criteria for crime news story selection in the Malaysian scenario. Using qualitative research methods applied to two prominent case studies and deriving crucial information from crime reporters through in-depth interviews, the study discovers that all crime stories are considered of importance but the severity of a crime defines news values and this is what ensures a story is selected. In terms of factors which affects news values, it can be said that the reporters assumption of what entails impact and of interest to the readers are what generally influences news values as well and to the fact that only if a story lacks major information and confirmation from reliable source that the story will not be done as the story does not have value. This social significance is important and is used to perceive connection to society where importance and impact play a vital role in deciding stories of value. Crime news has the opportunity to not only function as a communicative tool for society but communicates to society about everything representative of a criminal, the portrayal of threats, supporting responses, building norms and values whilst warning the public about the consequences of deviance and this can be clearly seen as an important reason to the affect it has on news values.